Ontological Study of The Classification of People in The Transfer of Land Rights in Realizing Legal Certainty - Rahadi Wasi Bintoro; Noor Dzuhaidah Dzuhaidah; Antonius Sidik Maryono; Sanyoto Sanyoto; Weda Kupita (Pandecta Research Law Journal, 2022)
Regulation of the Minister of State for Agrarian Affairs/ Head of the National Land Agency No. 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration contains regulations regarding the classification of the population in the preparation of a certificate of inheritance. At present, such arrangements are considered irrelevant, especially since there are already regulations concerning citizenship and population administration in a law. Therefore, this article discusses the ontological basis for regulating population classification in Indonesia. In order to answer these problems, three normative research approaches are used, in the form of a statutory approach, a historical approach and a conceptual approach. This study uses primary and secondary sources of legal material, which after an inventory has been processed and analyzed using a qualitative approach. The classification of the Indonesian population, when viewed from an ontological study, was a policy of the Dutch East Indies government to divide the Indonesian nation and reduce the power of customary law and Islamic law that developed in society. However, if judging from the existence of the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997, the classification of the population which has implications for the institution authorized to make certificates of inheritance is not due to the politics of dividing the Indonesian nation. This rule exists because it is still possible for people to submit to the law of inheritance of Burgelik Wetboek. This regulation in the statutory system is hierarchically positioned lower than the law. Even though this regulation is inferior and contradicts the Citizenship Law and the Population Administration Law, and therefore contradicts the principle of lex superior derogate legi inferiori, but to prevent a legal vacuum this Ministerial regulation is still in effect.